The Influence of Perception of Social Equality and Social Trust on Subjective Well-Being Among Rural Chinese People: The Moderator Role of Education - Gao, Shuang; Zhao, Jilun (Frontiers in Psychology, 2022)
The present study explored the moderation effect of education on the relationship between the perception of social equality and social trust and individuals’ subjective well-being in rural China. Data were derived from the nationally representative cross-sectional Chinese General Social Survey. After handling missingness, 5,911 eligible participants (age 18 years or older) from the 2015 wave were included in the model. We used logistic regression to test the hypotheses. We first tested the effect of the perception of social equality and social trust on subjective well-being. Then we added an interaction term to test the moderation effect of education in this relationship. The results show that education had a significant moderating effect on the association between general social trust and subjective well-being. While had no significant effect on the association between the perception of social equality, special social trust and subjective well-being. The perception of social equality had significant effects in both groups. The relationship between special social trust and subjective well-being in both groups was not significant. For the more educated group, general social trust had a significant and positive effect on subjective well-being.